Α4β2* Nicotinic Cholinergic Receptor Target Engagement in Parkinson Disease Gait–Balance Disorders. Issue 1 (26th May 2021) - Albin, Roger L.; Müller, Martijn L. T. M.; Bohnen, Nicolaas I.; Spino, Cathie; Sarter, Martin; Koeppe, Robert A.; Szpara, Ashley; Kim, Kamin; Lustig, Cindy; Dauer, William T.
Abstract : Objective: Attentional deficits following degeneration of brain cholinergic systems contribute to gait–balance deficits in Parkinson disease (PD). As a step toward assessing whether α4β2* nicotinic acetylcholine receptor (nAChR) stimulation improves gait–balance function, we assessed target engagement of the α4β2* nAChR partial agonist varenicline. Methods: Nondemented PD participants with cholinergic deficits were identified with [ 18 F]fluoroethoxybenzovesamicol positron emission tomography (PET). α4β2* nAChR occupancy after subacute oral varenicline treatment was measured with [ 18 F]flubatine PET. With a dose selected from the nAChR occupancy experiment, varenicline effects on gait, balance, and cognition were assessed in a double‐masked placebo‐controlled crossover study. Primary endpoints were normal pace gait speed and a measure of postural stability. Results: Varenicline doses (0.25mg per day, 0.25mg twice daily [b.i.d.], 0.5mg b.i.d., and 1.0mg b.i.d.) produced 60 to 70% receptor occupancy. We selected 0.5mg orally b.i.d for the crossover study. Thirty‐three participants completed the crossover study with excellent tolerability. Varenicline had no significant impact on the postural stability measure and caused slower normal pace gait speed. Varenicline narrowed the difference in normal pace gait speed between dual task and no dual task gait conditions, reduced dual task cost, and improved sustained attention test performance. We obtained identical conclusions in 28 participants with treatment compliance confirmed by plasma varenicline measurements. Interpretation: Varenicline occupied α4β2* nicotinic acetylcholine receptors, was tolerated well, enhanced attention, and altered gait performance. These results are consistent with target engagement. α4β2* agonists may be worth further evaluation for mitigation of gait and balance disorders in PD. ANN NEUROL 2021;90:130–142